Analysis of a Cement Storage bin Considering Lateral Forces using Staad.pro A Review - Shivam Nograiya; Rakesh Patel (International Journal of Scientific Research in Civil Engineering, 2021)
Concrete has the ability to conform to any desired shape and also it’s economical. Concrete proves to be a very useful material as it offers all the flexibilities in designing and construction of silos and bunkers which are required by any industry and foremost being in the economical limits. Importance of these storage structures has attracted the attention of many researchers worldwide to propose different load calculation methods and design considerations. ACI 1997 is the only available guidelines, for the design of silo and bunkers. In addition to it, different researchers proposed different methods to compute the loads of moving and loading material inside the silos and bunkers. In this study we are presenting review of literatures related to analysi of complex structures using softwares.